Changing Perceptions around Nontraditional Career Trajectories in Psychological Science. Issue 6 (June 2021) - Yudkin, Daniel A.; Stolier, Ryan M.; Lewis, Neil A.
Abstract : In a tightening job market, early-career researchers may consider employment opportunities outside academia. Yet there is the widespread belief that such employment experience is perceived negatively by academic hiring committees. Changing perceptions and practices around this issue would benefit these researchers and the field of psychology as a whole.